Limits of Design and Technique: Lina Bo Bardi Staircases - Muammer Yaman; Esma Eroğlu (VLC Arquitectura)
Staircases, a part of architectural circulation and structure, can become a unique design value with the application technique that directs design and functionality. However, here, attention is drawn to the directive nature of the technique rather than its perception as a deterministic attitude in design. Bo Bardi’s architectonic approach has placed her in a distinguished position among modern architects. The effect of the architect’s staircase design and application technique on building tectonics is worth examining. Thus, this study aims to examine the staircases of Lina Bo Bardi, where design and technique are dissolved in integrity. Bo Bardi’s staircases were examined in terms of meaning, form, function, and technique, with classification for material use. In this context, unique situations were observed in the design and technical applications of reinforced concrete, wood, and metal materials used in stairs. The fact that the place, technique, and the architect’s thought guided the design turned the staircase into a symbolic value and has made the staircase the founding element of the space. This approach, which does not consider design and technique independently, creates a strong reference for today that structural elements such as stairs can be produced as symbols in space.